Ether gas-sensor based on Au nanoparticles-decorated ZnO microstructures - Roberto López; Enrique Vigueras-Santiago; Alfredo Rafael Vilchis-Nestor; Victor Hugo Castrejón-Sánchez; Marco A. Camacho-López; Nayely Torres-Gómez (Results in Physics, 2017)
An ether gas-sensor was fabricated based on gold nanoparticles (Au-NPs) decorated zinc oxide microstructures (ZnO-MS). Scanning electron microscope (SEM) and high-resolution transmission electron microscope (HRTEM) measurements were performed to study morphological and structural properties, respectively, of the ZnO-MS. The gas sensing response was evaluated in a relatively low temperature regime, which ranged between 150 and 250 °C. Compared with a sensor fabricated from pure ZnO-MS, the sensor based on Au-NPs decorated ZnO-MS showed much better ether gas response at the highest working temperature. In fact, pure ZnO-MS based sensor only showed a weak sensitivity of about 25%. The improvement of the ether gas response for sensor fabricated with Au-NPs decorated ZnO-MS was attributed to the catalytic activity of the Au-NPs. Keywords: ZnO microstructures, Au nanoparticles, Ether, Gas sensor